Multimedia Design Of Gandrung Dance Using Android Application - Ciptaning Rahajeng Prawesti; Trisakti Trisakti; Setyo Yanuartuti (Gondang: Jurnal Seni dan Budaya, 2022)
In this era where technology is vastly developed, and even children can use or utilise smartphones, technology has become something general because of its ease. Therefore, technology can keep learning materials relevant to create suitable learning media for learners in this era. This study aimed to elaborate on the product's specifications and the learning media of Gandrung dance using the android application's developmental process. The research and Development method was used, and ADDIE-model was featured to assess the product's effectiveness. The data was collected using observation and interviews. The result of the study shows that the product development of Gandrung dance into a smartphone application consisting of Gandrung dance's graded material study from the synopsis, dance movements, makeup and wardrobe to quizzes. The three developmental processes that have been done up until this point are analysis, design, and development. The research problems were decided during the analysis stage, and the design and development stage was developed, developing the material or the product's display and bringing the idea into the product.